Characterization of a Novel RNA Virus Discovered in the Autumnal Moth Epirrita autumnata in Sweden - Joachim De Miranda; Harald Hedman; Piero Onorati; Jörg Stephan; Olof Karlberg; Helena Bylund; Olle Terenius (Viruses, 2017)
A novel, 10 kb RNA virus—tentatively named ‘Abisko virus’—was discovered in the transcriptome data of a diseased autumnal moth (Epirrita autumnata) larva, as part of a search for the possible causes of the cyclical nature and mortality associated with geometrid moth dynamics and outbreaks in northern Fennoscandia. Abisko virus has a genome organization similar to that of the insect-infecting negeviruses, but phylogenetic and compositional bias analyses also reveal strong affiliations with plant-infecting viruses, such that both the primary host origin and taxonomic identity of the virus remain in doubt. In an extensive set of larval, pupal, and adult autumnal moth and winter moth (Operophtera brumata) outbreak samples, the virus was only detected in a few adult E. autumnata moths as well as the single larval transcriptome. The Abisko virus is therefore unlikely to be a factor in the Fennoscandia geometrid population dynamics.